Biphasic Sarcomatoid Sweat Gland Carcinoma With Ductal Epithelial And Spindled Myoepithelial Cell Components (Malignant Mixed Tumor Of Skin). (28th October 2021) - Chiu, R; Tran, T; Miranda-Taylor, M; Bamdad, S; Jia, Y; Crabtree, M; Cornford, M; Yap, C; Peng, S
Abstract: Introduction/Objective: Sweat gland carcinomas are a group of malignant skin adnexal tumors that are difficult to diagnose due to their rarity, wide morphologic variation, and limited literature on diagnosis and classification. These tumors may appear bland and morphologically resemble benign skin adnexal tumors, or may appear poorly differentiated and mimic metastatic carcinoma especially from a breast primary. Biphasic sweat gland carcinomas are an even rarer entity, with only few cases reported in literature, and have been described to consist of a well- differentiated ductal epithelial component and a poorly differentiated, sarcomatoid, spindle cell component. Methods/Case Report: Our case report describes a 53 year old female referred to our institution for diagnosis of an excised skin lesion of the right upper arm, which had been slowly growing for 8 years. The histology revealed a biphasic malignant neoplasm involving the dermis and subcutis. The tumor consisted of an epithelial cell component with glandular and squamoid morphology and positive for CK5/6, CK7, and CAM5.2, and a spindled myoepithelial cell component with sarcomatoid morphology and positive for S100, vimentin, and p63. Stains for CK20, ER, PR, PAX8, CEA, and TTF1 were negative. The histological and clinical findings favored a primary skin adnexal tumor, rather than a metastatic lesion. The patient underwent wide local excision of the lesion given that margins of the original excision were indeterminate. The histology of this re-excision demonstrated the same biphasic tumor with ductal epithelial and sarcomatoid myoepithelial cell components positive for the same stains. Although margins were negative in this re-excision, 3-4 months later, the patient developed dyspnea with multiple new pulmonary and hilar masses discovered on imaging, and new-onset headache with a frontal lobe mass discovered on brain imaging. These masses were biopsied/resected, and revealed to be metastases of the original cutaneous tumor positive for the same markers. Results (if a Case Study enter NA): NA Conclusion: This case report describes a rare, diagnostically challenging case of a biphasic sweat gland carcinoma with ductal epithelial and sarcomatoid myoepithelial cell components, which demonstrated aggressive behavior with distant metastasis. These tumors are a clinicopathological quandary given their rarity and the paucity of literature on their characterization.